Semangat Kokutai dan Konsep Identitas Nasional dalam Kebijakan Nasional Film Jepang - Agnes Siwi Purwaning Tyas (Retorik: Jurnal Ilmu Humaniora, 2022)
The Greater East Asia Co-Prosperity Sphere was Japan’s imperialist attempt to control the economies of East Asia and Southeast Asia in the first half of the twentieth century. The constituents of the Sphere included Japan, Korea, China, Manchuria, and some territories in Southeast Asia. To increase agricultural production and strengthen its military force, Japan recruited people from its colonies. As the leader of the Sphere, Japan wished to establish its own identity as distinct from—and superior to—that of the West. Propaganda campaigns and media were carefully prepared to manipulate the thoughts and behavior of the people to contribute to the supposed goal of mutual prosperity in the Sphere, by providing labor power for industry and agriculture as well as the military. Films were central to the Japanese propaganda. From 1936 to 1945, films that contain political and ideological messages of the Japanese leadership were produced and circulated both inside and outside Japan. This research aims to illuminate the identity of the Japanese imperial power that was promoted through the propaganda films and show how the films highlighted nationalism and culture harnessed during the war period as constitutive of Japan’s national identity, or kokutai.